The impact of international megaproject social responsibility on satisfaction with the environmental compensation mechanism: The role of stakeholder participation - Zixuan Zeng; Yongtao Shen; Jijun Yang; Thammanoon Hengsadeekul (PLoS ONE, 2025)
Background Construction projects, particularly megaprojects, inherently entail substantial environmental and social challenges. Early research on megaproject social responsibility (MSR) has primarily focused on domestic contexts, such as China, and has explored resident satisfaction mainly through economic or policy lenses. However, these studies have paid limited attention to broader stakeholders, leaving a significant gap in understanding how MSR influences satisfaction with the environmental compensation mechanism (SECM), particularly in international settings. This study aims to fill this gap by examining how MSR at different stages of the project life cycle affects SECM and by analyzing the mediating role of stakeholder environmental activities participation (SEAP) in this relationship. The findings provide theoretical and empirical insights to enhance the design and implementation of environmental compensation in international megaprojects, thereby contributing to improved stakeholder satisfaction and sustainable development outcomes. Methods Grounded in life-cycle and stakeholder theories, this study investigated large-scale projects involving Chinese contractors in Thailand. We employed a two-stage questionnaire survey, beginning with a pilot study (n = 204) to validate the scales, followed by a main study (n = 398) for final analysis. Data were analyzed using factor analysis, Pearson correlation, and multiple linear regression. Results The results indicate that MSR has a significant positive effect on host-country residents’ satisfaction with the environmental compensation mechanism (SECM), with direct effects notably originating from the design and operational stages. Furthermore, stakeholder environmental activities participation (SEAP) partially mediates the relationship between MSR (across all its stages) and SECM. Conclusions This study enriches the literature by providing transnational empirical evidence on the role of MSR in improving SECM. It highlights the critical importance of the design and operation stages and confirms the mediating role of stakeholder participation. Practically, the findings offer valuable insights for international project managers and policymakers, emphasizing the strategic importance of engaging stakeholders in environmental activities to achieve sustainable development goals and enhance community satisfaction.